USULAN BIAYA PREVENTIVE MAINTENANCE DENGAN MENGGUNAKAN METODE MODULARITY DESIGN PADA MESIN RIPPLE MILL DI PT. INCASI RAYA POM - Henny Yulius; Fredy Tri Susanto (Sekolah Tinggi Teknologi Industri Padang, 2020)
PT. Incasi Raya POM, is a company engaged in the field of industry, which is engaged in palm oil processing. To maintain quality and productivity, important factors that must be considered are issues of maintenance (maintenance) of machines and production facilities and maintenance costs. Related to the party who gets the maintenance assignment, the policy needed for the best treatment system for the company. This research was conducted to discuss the problem of minimizing the cost of maintenance of existing press machines at PT. POM Raya Incasi. The method used to compare the maintenance costs of ripple mill machines is the modularity design that was distributed in the period 2019. With a total damage of each component as many as 39 damage. The total cost of repairing the machine at the cost of failure (CF) results in a total of Rp. 34,880,198, the cost of Preventive (CP) yields a total of Rp. 84,757,652, and at the cost of preventive modularity (CPM) get results with a total of Rp. 20,376,324 per year. Of the total costs, PT. Incasi Raya POM can find out how much the total maintenance cost for this ripple machine in the future, which allows the company to save budget in the process of ripple machine maintenance in the palm oil production process.